2022
DOI: 10.7759/cureus.25202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endoscopic Versus Open Lumbar Discectomy: A Multi-Center Retrospective Review Utilizing the American College of Surgeons’ National Surgical Quality Improvement Program (ACS-NSQIP) Database

Abstract: Introduction: Endoscopic techniques in spine surgery continue to gain popularity due to their potential for decreased blood loss and post-operative pain. However, limited studies have evaluated these techniques within the United States. Additionally, given the limited number of practitioners with experience in endoscopy, most current studies are limited by a lack of heterogeneity. Methods: The American College of Surgeons’ National Surgical Quality Improvement Program (ACS-NSQIP) database was querie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…This approach utilizes endoscopic visualization, and high-speed burrs [13]. A recent study demonstrated that ESS is superior to open discectomy regarding the rate of adverse events and total length of hospital stay [45]. It is possible to perform foraminoplasty and decompression of structures that may participate in the genesis of the degenerative disease of the segment approached (Figure 1) [46].…”
Section: Advantages Indications and Techniques In The Context Of Essmentioning
confidence: 99%
“…This approach utilizes endoscopic visualization, and high-speed burrs [13]. A recent study demonstrated that ESS is superior to open discectomy regarding the rate of adverse events and total length of hospital stay [45]. It is possible to perform foraminoplasty and decompression of structures that may participate in the genesis of the degenerative disease of the segment approached (Figure 1) [46].…”
Section: Advantages Indications and Techniques In The Context Of Essmentioning
confidence: 99%
“…In patients with lumbar disc herniation, microendoscopic discectomy and open microdiscectomy are used to treat pain caused by lumbar radicular compression in patients whose symptoms persist despite medication and other nonsurgical interventions. Microendoscopic discectomy is being used more widely because it offers a shorter recovery period and its clinical results seem to be comparable to those of open microdiscectomy [2, 8], but whether the short-term benefits come at a cost in terms of longer-term problems (such as reoperations) remains unknown [4]. In particular, whether the smaller approach results in more-severe damage to the remaining disc has not been characterized, and the “microendoscopic” and “open” techniques include adaptations that have varied across studies on the topic.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…While traditional open discectomy is known for its effective outcomes, the procedure's invasiveness and associated complications often result in extended recovery periods [3]. Consequently, there has been a shift toward minimally invasive techniques to reduce surgical morbidity [4].…”
Section: Introductionmentioning
confidence: 99%